Addendum zu Methanol [BAT value documentation in German language, 2019]. Issue 4 (13th November 2019) - Kreis, P.; Brinkmann, B.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2018, the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has lowered the maximum concentration at the workplace (MAK value) to 100 mL methanol/m 3 . The BAT value was correlated to the MAK value. Therefore, the BAT value has to be re‐evaluated. After 8‐hour exposure of test persons to 100 mL methanol/m 3 with physical activity, a concentration of 15 mg methanol/L urine was measured. This is in line with the results of a field study in which a methanol concentration of approximately 100 mL/m 3 corresponded to around 20 mg methanol/L urine. Therefore, the BAT value has now been set to 15 mg methanol/L urine. Sampling time is at the end of exposure or the end of the working shift, for long‐term exposure at the end of the shift after several shifts.